Research on Temperature Field and Ampacity of the Bottleneck Section of the Bundled Submarine Cable in Marginal Oilfields - DAI Guo-hua; WANG Wan-xu; CHEN Feng-bo; JIN Qiu; GAO Yang; WANG Hai-tao (Journal of Harbin University of Science and Technology)
The cluster submarine cable is an important equipment for the offshore oil development platform, which has the characteristics of large cross-section, complex structure, long laying path and complex and changeable characteristics.The complex and changeable laying environment makes the rated current carrying capacity of the cluster submarine cable affected by many environmental factors.Through multi-physics finite element software, the rated current carrying capacity of the cluster submarine cable is calculated and analyzed considering many natural factors.It can be concluded that the J-shaped pipe laying section is the bottleneck section of the rated current carrying capacity of the cluster submarine cable.Among environmental factors, the water level changes caused by tidal fluctuations will affect the rated current carrying capacity of the bottleneck section of the cluster submarine cable.The higher the water level, the higher the rated current carrying capacity, and vice versa.The main natural factor of the current carrying capacity, with the increase of sunlight irradiation, the rated current carrying capacity of the cluster submarine cable in the bottleneck section drops rapidly, and the maximum drop rate exceeds 30%. By using a low-power pump to inject water into the J-shaped pipe, the influence of environmental factors on the rated current carrying capacity of the cluster submarine cable can be effectively improved, and the current capacity of the bottleneck section of the cluster submarine cable can be effectively improved.